Intelligent computational paradigms in earthquake engineering - Lagaros, Nikos D. 1970-; Tsompanakis, Yiannis 1969- (Gale virtual reference library, 2007)
"This book contains contributions that cover a wide spectrum of very important real-world engineering problems, and explores the implementation of neural networks for the representation of structural responses in earthquake engineering. It assesses the efficiency of seismic design procedures and describes the latest findings in intelligent optimal control systems and their applications in structural engineering"--Provided by publisher.